2015
DOI: 10.1001/jamasurg.2014.2895
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Trends in Mastectomy for Early-Stage Breast Cancer

Abstract: In the past decade, there have been marked trends toward higher proportions of BCS-eligible patients undergoing mastectomy, breast reconstruction, and bilateral mastectomy. The greatest increases are seen in women with node-negative and in situ disease. Mastectomy rates do not yet exceed current American Cancer Society/American College of Surgeons Commission on Cancer accreditation benchmarks. Further research is needed to understand factors associated with these trends and their implications for performance m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
448
2
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 613 publications
(481 citation statements)
references
References 20 publications
19
448
2
12
Order By: Relevance
“…These two studies were the first in a string of studies examining the increasing CPM rate across the US (Table 1). 11,[14][15][16][17][18][19][20] In 2010, a report from the National Cancer Data Base (NCDB) showed an increase in CPM from 0.4% in 1998 to 4.7% in 2007. 16 A 2011 study from Memorial Sloan Kettering reported that 6.7% mastectomy patients underwent CPM in 1997, which increased to 24.2% in 2005.…”
Section: Trends In Cpmmentioning
confidence: 99%
“…These two studies were the first in a string of studies examining the increasing CPM rate across the US (Table 1). 11,[14][15][16][17][18][19][20] In 2010, a report from the National Cancer Data Base (NCDB) showed an increase in CPM from 0.4% in 1998 to 4.7% in 2007. 16 A 2011 study from Memorial Sloan Kettering reported that 6.7% mastectomy patients underwent CPM in 1997, which increased to 24.2% in 2005.…”
Section: Trends In Cpmmentioning
confidence: 99%
“…Moterų, kurioms buvo galima atlikti krūtį tausojančias operacijas, vietoje jos pasirinkusių mastektomijas, skaičius išaugo nuo 34,3% (1998 m.) iki 37,8% (2011 m.). Taip pat abipusę mastektomiją esant vienos krūties onkologiniam susirgimui 2011 m. pasirinko 11,2% moterų, kai 1998 m. tokių moterų buvo tik 1,9% [3,4]. Egzistuoja keletas teorijų tokiam radikaliam moterų pasirinkimui paaiškinti.…”
Section: įVadasunclassified
“…Krūtį atstatančių operacijų skaičius JAV per 15 metų išaugo nuo 11,6% (1998 m.) iki 48% (2013 m.). Mažesnę tikimybę atstatyti krūtį po jos pašalinimo turėjo nebaltaodės, neturinčios privataus draudimo, gyvenančios že-mesnio ekonominio išsivystymo zonose bei žemesnį išsilavinimą turinčios moterys [6]. Klaipėdos universitetinėje ligoninėje (toliau KUL) 2015 m. atliktos studijos duomenimis, kuomet buvo tiriama moterų, kurioms atlikta mastektomija, gyvenimo kokybė plantais ar plėtikliais) ir mišrus.…”
Section: įVadasunclassified
“…to include those with advanced breast cancer, close tumornipple distance, neoadjuvant chemotherapy (NAC), and postmastectomy radiation therapy who underwent IBR [2,[7][8][9][10]. This study sought to analyze the oncologic outcomes between TM only and IBR following NSM or non-NSM (NNSM) in a population matched by age at operation, year of operation, pathologic stage, estrogen receptor (ER)/progesterone receptor (PR) status, and human epidermal growth factor receptor 2 (HER2) status.…”
Section: Oncologic Outcomes After Immediate Breast Reconstruction Folmentioning
confidence: 99%